Unofficial city names of Bydgoszcz - Czachorowska, Magdalena (Name – style – text: A jubilee book dedicated to Professor Elżebieta Umińska-Tytoń, 2023)
The article is intended to be a research reconnaissance, an attempt to face the variable and unstable resource of unofficial urban onims, to signal methodological problems that may arise during proper research, to show the possibilities and limitations of the researcher of this issue. Already from a superficial analysis prepared on a small set of colloquial urban names, difficulties arise related to the generacy, hermetic, openness of the set and fluidity of names different from official ones. The analysis led to the following conclusions that urban colloquial nomenclature arises by modifying official names through ellipses, phonetic changes, inflectional changes, etc. — existing names or through doublets — previous names, changed; and without reference to the circulation of official names in the form of urbanonyms created on the basis of associations, language games or language jokes.